Female workforce participation in the Australian oil and gas industry—a global comparison - Marinelli, Melissa; McGrath, Kristy (Australian Petroleum Production and Exploration Association, 2012)
As the Australian oil and gas industry faces a continued shortage of skilled employees, increasing the representation of women in this industry is a business imperative. Economic success and competitive advantage may depend on attracting and retaining the skills of women. This extended abstract presents the current picture of women in oil and gas in Australia, with comparisons drawn to Canada and Norway. The focus is on current research related to female participation in the sector and the initiatives being undertaken to improve this across the international context. The paper concludes with a case study about the key success factors and challenges in establishing “Women@Clough” - a corporate initiative to increase female participation at Clough Limited.